Under construction and highly contested: Islam in the post-Soviet Caucasus. Issue 9 (1st September 2016) - Bedford, Sofie; Souleimanov, Emil Aslan
Abstract: While scholarship on Islam in the Caucasus has focused on the late Soviet religious revival – the rise of Salafi jihadism and religious radicalisation in the northern part of these strategic crossroads – no study to date has addressed the discursive struggle over the social functions of regional Islam. This article deconstructs these discourses in order to examine the very varying, and often conflicting, representations of Islam advocated by various actors across the region and within particular republics. The article highlights the contested functions of regional Islam against the background of a religious revival that is still a work in progress.